1998
DOI: 10.1128/aem.64.2.763-767.1998
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Nucleotide Sequencing of a Staphylococcus aureus Gene Encoding a Branched-Chain-Amino-Acid Transporter

Abstract: We recently characterized a transposon-induced NaCl-sensitive mutant of Staphylococcus aureus (U. Vijaranakul, M. J. Nadakavukaren, D. O. Bayles, B. J. Wilkinson, and R. K. Jayaswal, Appl. Environ. Microbiol. 63:1889–1897, 1997). To further characterize this mutant, we determined the nucleotide sequence at the insertion site of the transposon on the S. aureuschromosome. Nucleotide sequencing revealed a 1,326-bp open reading frame (ORF442) encoding a hydrophobic 442-amino-acid polypeptide with a calculated mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Various known S. aureus gene clones available in our laboratory were used to explore the location of znt on the bacterial chromosome. These include lytI (15), lytM (24), atl (21), brnQ (30), and others. Dot blot studies showed hybridization of znt with the cosmid clones containing the lytI gene, thus mapping it within the SmaI-B fragment of S. aureus (14).…”
Section: Resultsmentioning
confidence: 99%
“…Various known S. aureus gene clones available in our laboratory were used to explore the location of znt on the bacterial chromosome. These include lytI (15), lytM (24), atl (21), brnQ (30), and others. Dot blot studies showed hybridization of znt with the cosmid clones containing the lytI gene, thus mapping it within the SmaI-B fragment of S. aureus (14).…”
Section: Resultsmentioning
confidence: 99%
“…Members of the DUF1185 family are also present in several human and animal pathogens from burkholderia and bordetella, as well as clostridia, where their genome location on virulence islands suggests a possible role in pathogenesis (Nierman et al, 2004). In some pathogenic bacteria, one of the modes of BCAA transportation is thought to be sensitive to stress induced by changes in osmolarity, pH or temperature (Vijaranakul et al, 1998). In this context, BB2672 and its homologs might present attractive drug targets since, similar to chorismate mutases, DUF1185 homologs are not found in mammals.…”
Section: Similarity To Other Proteinsmentioning
confidence: 99%
“…Although the rate of synthesis of most cellular proteins is decreased under these conditions, the rate of synthesis of certain cellular proteins, which may represent osmotic stress proteins or general stress proteins, increases in response to a decrease in growth medium a w (5,(11)(12)(13)(14)(15). Curiously, despite the great importance of the stress tolerance response of S. aureus, the identity of only a few potential stress proteins of S. aureus has been established (2,41,42).…”
mentioning
confidence: 99%